Do We Really Need Additional Contrast-Enhanced Abdominal Computed Tomography for Differential Diagnosis in Triage of Middle-Aged Subjects With Suspected Biliary Pain. Issue 7 (February 2015) - Hwang, In Kyeom; Lee, Yoon Suk; Kim, Jaihwan; Lee, Yoon Jin; Park, Ji Hoon; Hwang, Jin-Hyeok
Abstract : Abstract: Enhanced computed tomography (CT) is widely used for evaluating acute biliary pain in the emergency department (ED). However, concern about radiation exposure from CT has also increased. We investigated the usefulness of pre-contrast CT for differential diagnosis in middle-aged subjects with suspected biliary pain. A total of 183 subjects, who visited the ED for suspected biliary pain from January 2011 to December 2012, were included. Retrospectively, pre-contrast phase and multiphase CT findings were reviewed and the detection rate of findings suggesting disease requiring significant treatment by noncontrast CT (NCCT) was compared with cases detected by multiphase CT. Approximately 70% of total subjects had a significant condition, including 1 case of gallbladder cancer and 126 (68.8%) cases requiring intervention (122 biliary stone-related diseases, 3 liver abscesses, and 1 liver hemangioma). The rate of overlooking malignancy without contrast enhancement was calculated to be 0% to 1.5%. Biliary stones and liver space-occupying lesions were found equally on NCCT and multiphase CT. Calculated probable rates of overlooking acute cholecystitis and biliary obstruction were maximally 6.8% and 4.2% respectively. Incidental significant finding unrelated with pain consisted of 1 case of adrenal incidentaloma, which was also observed in NCCT. NCCT might be sufficient to detect life-threatening or significant disease requiring early treatment in young adults with biliary pain.